Erectile dysfunction and micturition disorders in patients with metabolic syndrome - S. V. Shkodkin; A. V. Polishchuk; S. V. Chirkov; A. F. Khuseynzoda; M.Z. Abed Alfattah Zubaydi (Вестник урологии)
Introduction. The aetiology and pathogenesis of lower urinary tract symptoms, chronic pelvic pain syndrome, and erectile dysfunction are not fully understood. Metabolic syndrome (MS) is an independent factor in these disorders.Purpose of the study. To determine the significance of metabolic syndrome in the development and course of dysuria, chronic pelvic pain syndrome and erectile dysfunction.Materials and methods. The study involved 115 men aged 40 - 60 years. Patients are divided into two groups based on the presence or absence of proven metabolic syndrome. The age of patients in the main group (n = 86) was 52.0 ± 3.5 years. A control group (n = 29) — men without metabolic syndrome at the age of 50.5 ± 2.4 years. Patients were questioned using questionnaires IPSS (International System for the Summary Assessment of Diseases of the Prostate), ICEF-5 (International Index of Erectile Function). An objective (physical) examination was performed. Laboratory diagnostics included the determination of the following indicators: total testosterone, albumin, SHBG (sex hormonebinding globulin), the level of free testosterone was calculated based on the three previous indicators, LH (luteinizing hormone), insulin, glucose, glycosylated haemoglobin, lipid profile. All patients underwent uroflowmetry, bladder ultrasound for determination of residual urine volume, prostate TRUS (transrectal ultrasound) with Doppler blood flow. The significance of the differences was determined by the nonparametric Mann-Whitney test; the differences were considered statistically significant if the probability was greater than 95%.Results. Patients with MS had statistically significant more pronounced symptoms on the IPSS scale and a lower QoL index. According to uroflowmetry, the maximum flow rates in the study group were significantly lower than the control. There was an increase in the duration of urination in patients with MS. Patients with MS presented more pronounced complaints of erectile dysfunction according to the IIEF5 scale in comparison with the control group of observation. The data obtained make it possible to associate MS with the risk of developing lower urinary tract symptoms and urgency in men.Conclusion. Metabolic syndrome acts as an independent factor in erectile dysfunction and hypogonadism, which leads to urinary disorders.